Ascorbic acid antagonizes the sedative effect of diazepam possibly through inhibition of GABA(AÏâ‚) and GABA(B1) receptors - Islam, Muhammad Torequl; Molla, Shamim; Zihad, S. M. Neamul Kabir; Umer, Muhammad; Rahman, Md. Shamim; Zaman, Farhana; Das, Apu Kumar; Afzal, Muhammad Inam; Salehi, Bahare; Akter, Mst. Shahina; Mubarak, Mohammad S.; Martins, Natália; et al. (Cellular and Molecular Biology, 2020)
Gamma-aminobutyric acid (GABA) receptors belong to a ligand-gated ion channels family and are markedly expressed at the axon terminals of retinal bipolar cells. Ascorbic acid (AA), a known and vital antioxidant in the brain can modulate GABA receptors. We postulate that AA would antagonize benzodiazepines’ effect via GABA receptor(s) interacting pathway. Here, we evaluated the modulatory sedative effect of AA on diazepam (DZP)’s anxiolytic effects in Swiss albino mice. The anxiolytic study was accomplished by using open-field, hole-board, and by swing and light-dark tests taking DZP as a standard anxiolytic drug. To understand the possible modulatory effects of AA, animals were co-administered with AA and DZP and/or its antagonist flumazenil (FLU). Additionally, an in-silico study was undertaken against GABA(A1), GABA(B1), and GABA(AÏâ‚) receptors. Data suggest that AA at 25 mg/kg (i.p.) increased (p<0.05) the number of field cross, rearing, number of hole cross, and swing and residence, while decreased grooming and dark residence parameters as compared to the control and DZP groups. In addition, AA and/or FLU combined with DZP (2 mg/kg, i.p.) reversed DZP-mediated sedative effects in mice. Results from in silico study suggest that AA has good interactions with GABA(AÏâ‚) and GABA(B1) receptors. In conclusion, DZP is a GABA receptor agonist and AA may reverse DZP-mediated sedative effects in a non-competitive binding fashion in mice through inhibition of GABA(AÏâ‚) and GABA(B1) receptors.